New species of Annulatascus and Saccardoella from the Philippines - Cai L. (2014)
Annulatascus liputii sp. nov. and Saccardoella minuta sp. nov. found on woody substrates submerged in the Liput River in the Philippines, are described, illustrated and compared with similar taxa. The confusion surrounding the genus Saccardoella is also discussed. A key to species of Saccardoella is provided.